Incremental conductance MPPT method for PV systems - Safari, A.; Mekhilef, Saad (2011)
This paper presents incremental conductance method for maximum power point tracking (MPPT) using DC-DC cuk converter. Comprehensive analysis and simulation of KC85T solar module and equivalent electric circuit are provided while effects of various environmental conditions on the PV module behavior is investigated. In order to fully understand the PV module working specifications fundamental characteristics of PV cells are discussed. Block diagram model of a PV module was developed in Simulink for plotting the curves. KC85T solar module is used in simulations and results indicate speed and accuracy of the proposed system.